Analysis of Influencer Communication Strategies in Building Investment Awareness on Social Media Platforms - Antania Hanjani Nugraheni; Yanti Haryanti (LEGAL BRIEF, 2024)
The phenomenon of digital asset investment emerged in the midst of the ongoing pandemic, one of which is investing in crypto coins. This research aims to identify and find out how effective influencer communication strategies on social media platforms are in building investment awareness. This research uses descriptive qualitative research methods. The results of this research are First, the communication strategy used by influencers with (1) influencers providing direction that investment is a good and beneficial thing. (2) the influencers who are followed have an educational background that is suitable as a financial planner who is an expert in their field (3) The number of influencers who contribute and persuade the general public from all economies and the messages conveyed are quite informative (4) starting to provide an understanding of investment through social media (5) ) Providing education regarding decisions to increase literacy regarding investment, especially trading. Second, the communication strategy used by influencers on social media platforms is effective because the influencer has the appropriate educational background as a financial planner who is an expert in their field